Android application for USDA (U.S. Department of Agriculture) structural design software - Addanki, Nikhita (Kansas State University, 2014)
The computer industry has seen a growth in the development of mobile applications over the last few years. Tablet/Mobile applications are preferred over their desktop versions due to their increased accessibility and usability. Android is the most popular mobile OS in the world. It not only provides a world-class platform for creating several apps, but also consists of an open marketplace for distributing them to Android users everywhere. This openness has led to it being a favorite for consumers and developers alike, thereby leading to a strong growth in app consumption. The main objective of the project is to design and develop an Android software application for USDA (U.S. Department of Agriculture) structural design that can be used on Android tablets. The different components of USDA that can be designed using this application are SingleCell, TwinCell, Cchan, Cbasin and Drpws3e. The USDA (U.S. Department of Agriculture) structural design application was previously developed using FORTRAN. But FORTRAN is not supported by Android Tablets. So, F2J Translator software was used to convert the FORTRAN source files to java source files which are supported by Android. Also, many other formatters such as CommonIn, CommonOut, and SwapStreams were used to translate some common blocks of FORTRAN code that cannot be translated by F2J Translator. The developed Android software allows users to access all different components of USDA structural design. Users can either directly enter the data in the forms provided or upload a file that already has data stored in it. When the application is run, the output can be accessed as a PDF file. Users can even send the output of a particular component to their personal email address. This output provided by the software application is helpful for design engineers to implement new structural designs.
Keywords: Android; U.S Department of Agriculture; FORTRAN; Translator; Android application; Computer Science (0984)